Untargeted metabolomics to analyze alterations in two-dimensional graphdiyne–copper nanocomposite on the metabolic reprogramming of prostate cancer. (1st January 2023) - Zhang, Yixun; Xie, Wenjie; Lin, Jundong; Zhuo, Yangjia; Zou, Zhihao; He, Huichan; Xu, Qianfeng; Tang, Zhenfeng; Tan, Huijing; Liu, Ren; Deng, Yulin; Cai, Shanghua; et al.
Abstract: Prostate cancer (PCa) is a common type of cancer in men worldwide. Metabolic reprogramming is an important factor in its pathogenesis. Two-dimensional (2D) nanomaterials have tremendous potential for cancer treatment owing to their unique physicochemical properties. However, very few studies have focused on the metabolic reprogramming mechanisms of PCa using 2D nanomaterials. In this study, for the first time, 2D graphdiyne (GDY) was used as a template to immobilize copper (Cu) ions to form a novel nanocomposite (GDY–Cu). GDY provides a large π -conjugated architecture that spatiotemporally restricts Cu ions spatiotemporally to realize the functional moiety of Cu ions as tumor therapeutics. The GDY–Cu nanocomposite with a 2D morphological structure was characterized using a transmission electron microscopy (TEM) and atomic force microscopy. The distribution of Cu loaded on the GDY was confirmed by high-resolution TEM with energy-dispersive x-ray spectroscopy analysis. In vitro and in vivo, GDY–Cu exhibits a good antitumor effect and is associated with specific metabolic reprogramming characteristics of PCa. In this study, the effect of GDY–Cu on the metabolic reprogramming of PCa cells was analyzed using untargeted metabolomics. Differences in metabolites in DU145 cells treated with GDY–Cu were analyzed by clustering and target analysis using bioinformatics methods. GDY–Cu inhibited the growth of PCa cells by decreasing the expression levels of acetyl-CoA carboxylase and cytoplasmic acetyl-CoA synthase, which inhibits the synthesis of related fatty acids and lipid metabolism. These results indicated that GDY–Cu inhibits the growth of PCa cells mainly via lipid metabolic pathways. At present, combinatory therapeutic modalities based on GDY and Cu are in their infancy. Further exploration is required to promote the development of 2D nanocomposite combinatory therapeutic modalities based on metabolic reprogramming.